Manifestation of deformation effect in band spectra in crystals with inhomogeneous bonding - Bercha, D.M.; Rushchanskii, K.Z.; Slipukhina, I.V.; Bercha, I.V. (Condensed Matter Physics, 2003)
The effect of the shear strains on the energy spectrum of the strongly
anisotropic SbSI crystal has been investigated by group-theoretical method
in combination with the Pikus method of invariants. The first-principles local
density approximation has been implemented to determine the band structure
of the crystal. Ab initio calculations of the band structure have shown
an exact localization of twofold degenerate maximum of the valence band
in the T point. It turned out that the shear strains result in the band topology
changes in the vicinity of the T point and the k -linear term appears in the
corresponding dispersion law. Теоретико-груповим методом в поєднанні з методом інваріантів
Пікуса досліджено вплив зсувових деформацій на енергетичний
спектр сильно анізотропного кристала SbSI. Для визначення зонної
структури кристала було застосовано розрахунки з перших принципів з використанням локального наближення. Дослідження зон-
ної структури вказали на точну локалізацію двократно виродженого
максимума валентної зони в точці Т. Виявилося, що зсувові деформації приводять до зміни топології зон в околі точки Т, а у відповідному законі дисперсії з’являється k -лінійний член.